2006
DOI: 10.1177/0095798406290466
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Religious Coping and Suicidal Behaviors Among African American Adolescents

Abstract: This study investigated whether hopelessness and depression were risk factors for suicidal thoughts and behaviors in African American adolescents and looked at whether religious participation and religious coping protected these students from suicidality. Participants were 212 African American high school students (133 females, 79 males). The results of multiple and logistic regression analyses found that hopelessness and depression were risk factors for suicidal ideation and attempts. Religious coping style w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 55 publications
6
84
0
Order By: Relevance
“…Our finding that religiosity was an important protective factor against suicide is consistent with prior theories that suggested African Americans have strong convictions against suicide due to religious beliefs (Early & Akers, 1993;Gibbs, 1997;Molock et al, 2006). Many participants emphasized the importance of reading the Bible and praying, which seemed to provide a sense of agency and calm.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding that religiosity was an important protective factor against suicide is consistent with prior theories that suggested African Americans have strong convictions against suicide due to religious beliefs (Early & Akers, 1993;Gibbs, 1997;Molock et al, 2006). Many participants emphasized the importance of reading the Bible and praying, which seemed to provide a sense of agency and calm.…”
Section: Discussionsupporting
confidence: 89%
“…Culture can be defined as the characteristics and knowledge of a particular group of people, defined by language, religion, social habits, music, and arts, and expressed by shared patterns of behaviors and interactions, cognitive constructs, and understanding learned by socialization (Leong & Leach, 2008). It has been proposed that, for many African Americans, the most important protective factor against suicide is religiosity, or a strong conviction condemning suicide as sinful (Early & Akers, 1993;Gibbs, 1997;Molock, Puri, Matlin, & Barksdale, 2006). Consistent with this notion, researchers have found that lower suicide rates among African Americans are partially explained by a strong belief that suicide is an unacceptable option no matter how dire one's life circumstances (Early & Akers, 1993;Stack, 1998).…”
mentioning
confidence: 99%
“…The strongest relationships were found between the centrality of religiosity and emotion-oriented coping and positive religious coping. In this sense, the findings are consistent with views expressed by Horwitz et al [31], who pointed out that religion may influence coping through emotional reactions, and also by Pargament et al [19], who stressed the role of positive religious cognitions in coping mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…Positive reinterpretations of negative events were especially noticeable in religious and spiritual coping. Research demonstrated that self-directed religious coping was related to increased hopelessness, depression and suicide attempts, whereas collaborative coping was related to increased reasons for living [31].…”
Section: Religiousness and Copingmentioning
confidence: 99%
See 1 more Smart Citation